2005
DOI: 10.1007/s10546-005-2078-7
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparisons of Experimental Convective Heat Transfer Coefficients and Mass Transfer Coefficients of Urban Surfaces

Abstract: The convective heat transfer coefficient (CHTC) of an urban canopy is a crucial parameter for estimating the turbulent heat flux in an urban area. We compared recent experimental research on the CHTC and the mass transfer coefficient (MTC) of urban surfaces in the field and in wind tunnels. Our findings are summarised as follows.(1) In full-scale measurements on horizontal building roofs, the CHTC is sensitive to the height of the reference wind speed for heights below 1. 5 m but is relatively independent of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…1). Surface albedo for infinite twodimensional street canyons (Arnfield 1982;Sievers and Zdunkowski 1985;Sakakibara 1996;Masson 2000;Kusaka et al 2001;Martilli Table 1 Reviews on urban meteorology published after 2000 Reference Topic Roth (2000) atmospheric turbulence over cities Jauregui (2000) tropical urban climatology Fernando et al (2001) air circulation and dispersion in cities Arnfield (2003) comprehensive review of urban climate, 1980climate, -2003climate, Shepherd (2005 urban-induced rainfall, Hagishima et al (2005 transfer coefficients of urban surfaces Oke (2006) scientific communication in urban climates Grimmond (2006) measuring and observing the urban atmosphere Masson (2006) urban surface modeling Kanda (2006b) physical scale modeling of the urban climate Mills (2006) sustainable settlements Best (2006a) weather forecasts for city dwellers Li et al (2006) CFD of flow and dispersion in street canyons Fig. 1.…”
Section: Urban Surfaces As the Bottommentioning
confidence: 99%
See 1 more Smart Citation
“…1). Surface albedo for infinite twodimensional street canyons (Arnfield 1982;Sievers and Zdunkowski 1985;Sakakibara 1996;Masson 2000;Kusaka et al 2001;Martilli Table 1 Reviews on urban meteorology published after 2000 Reference Topic Roth (2000) atmospheric turbulence over cities Jauregui (2000) tropical urban climatology Fernando et al (2001) air circulation and dispersion in cities Arnfield (2003) comprehensive review of urban climate, 1980climate, -2003climate, Shepherd (2005 urban-induced rainfall, Hagishima et al (2005 transfer coefficients of urban surfaces Oke (2006) scientific communication in urban climates Grimmond (2006) measuring and observing the urban atmosphere Masson (2006) urban surface modeling Kanda (2006b) physical scale modeling of the urban climate Mills (2006) sustainable settlements Best (2006a) weather forecasts for city dwellers Li et al (2006) CFD of flow and dispersion in street canyons Fig. 1.…”
Section: Urban Surfaces As the Bottommentioning
confidence: 99%
“…Parameterization of local transfer coefficients for momentum and scalars between surfaces (e.g., roof, street, walls) and a reference height requires more than a one-dimensional approximation. However, a compilation of experimental data suggests that such coefficients largely differ case by case and thus are difficult to arrange in a simple formulation (see Hagishima et al 2005 for review).…”
Section: Recent Technique a Simulation Techniquementioning
confidence: 99%
“…Unlike their natural counterparts (bare soils or vegetation), hydrological models for urban pavements or impervious roofs should be capable of resolving the water-holding capacity of impervious media, which regulates the evaporation for the major fraction of urban surfaces (Yamanaka et al, 1997;Andersen et al, 1999;Hagishima et al, 2005;Borselli and Torri, 2010;Nakayama and Fujita, 2010;Abahri et al, 2011). Therefore, urban hydrological models, in addition, need to incorporate the unique feature of evaporation arising from surfaces with engineered materials.…”
Section: Introductionmentioning
confidence: 99%
“…A clear overview of the different experimental techniques to determine these CHTCs and their limitations was given by Hagishima et al [9]. CHTCs were also determined for greenhouses of which a concise review can be found in Roy et al [10].…”
Section: Full-scale Experimentsmentioning
confidence: 99%
“…A recent and extensive review on CHTC correlations for applications towards solar collectors was provided by Palyvos [8]. Hagishima et al [9] and Roy et al [10] included a more concise overview of CHTC correlations in their work, from the viewpoint of urban canopy modelling and the greenhouse climate, respectively. In the overview in this paper, primarily additional information to existing reviews will be presented, while for other information, reference will be made to these earlier reviews.…”
Section: Introductionmentioning
confidence: 99%